Hoop in 'n tyd van wanhoop : 'n akrostiese vertaling van Klaagliedere - Spuy, Roelie van der (Journal for semitics, 2009)
In this paper the possibility of preserving some aspects of the uniqueness of Biblical Hebrew acrostic literature in a translation is discussed and demonstrated. After focusing on the communication value of the structure in which literature is presented, the value of semantic domains in making a translation is shortly highlighted. Then a few key terms are discussed and finally the author's effort to translate Lamentations as an alphabetical acrostic unit is presented. The message and form of a poem form a cognitive unit. In making an acrostic translation the translator has to overcome not only the difficulty of finding a word belonging to the right semantic domain, but finding a translation equivalent that starts with the right letter of the alphabet.